The Implementation Science of Financial Intelligence in Evidence-Based Medicine Using Select Criteria Mechanism as Treatment Process towards Healthcare Corporate Governance - Llarena, Zharama (American Journal of Health, Medicine and Nursing Practice, 2023)
Purpose: Implementation science is the broader aspect of corporate social responsibility (CSR) translating healthcare education to clinical research and practice for public health and patient safety encompassing the hierarchy of evidence-based medicine (EBM), hence, serving as an integrative method of combing CSR towards healthcare corporate governance. This paper aims to model EBM under principles of valid contract formation as compliance to CSR theories of promoting positive health outcomes of patient safety leading to financial success and lessening the risks of mortality cases. Methodology: The elements of valid contract formation and sources of errors are the systematic plan for behavioral guidance of EBM practice. These determinants are crucial in refining the clinical judgment of medical experts together with other healthcare professionals in support with high-ranking databases of research publication, resulting to a greater impact of positive health outcomes of patient safety under "judicious" application of CSR. These principles of contract law are integrated for "measuring" the EBM's financial success towards healthcare corporate governance. Findings: EBM is a scientific approach to handle medical cases and reports towards patient safety under clinical judgment of medical expert and healthcare team in corroboration with reliable sources of databases for medical research and review for reducing death rates in healthcare setting. SELECT Criteria Mechanism elucidated EBM as implementation science integrating CSR for behavioral compliance to healthcare corporate governance. First, the modeling of CSR as method to comply with EBM delineates the elements formed for valid contract formation in producing an "ethical" standard as responsibility for optimal patient safety as bargained promise under acceptance of the clinical team. Second, the illustration of the healthcare corporate governance in EBM practice as theory "measures" the reduction of healthcare expenditures from the exhibited means of diminishing mortality cases. Therefore, implementation science serves as an initiation for remediation process of reducing risks of death cases. Recommendation: Implementation science is very important in EBM practice in treating ways of lessening the probability of mortality cases under "ethical" or "judicious" patient safety guidelines as corporate social responsibility. Hence, it is recommended to develop systems for behavioral guidance in a more organized plan of targeting death reduction cases towards financial intelligence as fulfillment in implementation science.